PENDIDIKAN ISLAM DI INDONESIA SETELAH MERDEKA - Yuliani Yuliani; Edy Purwanto (ADIBA : JOURNAL OF EDUCATION, 2022)
This article discusses Islamic education in Indonesia after independence. This study discusses using the literature review method. And the process of the stages of work include: First, literature review method which is the process of collecting data sources for Islamic educational studies after independence, as for the content of this research about the development of Islamic education after independence where the pesantren education system and madrasah in order to produce skilled workers who are ready to enter the world of work. Islamic boarding schools (pondok pesantren) have great potential to create new entrepreneurs and grow the small and medium industry (IKM) sector. For this reason, the government is intensively implementing the Santripreneur program as an effort to optimize the provision of employment in the region or village while reducing the unemployment rate and encouraging equitable distribution of community welfare.